PHYSICAL REHABILITATION OF FOOTBALL PLAYERS AFTER REMOVAL OF THE ANKLE JOINT WITH KINESIOTHERAPY - Charbel , Youssef; Pіdkopay Т. V.; Pіdkopay D. O. (Rehabilitation and Recreation, 2023)
The high level of active professional activity of qualified athletes dictates the need for a quick and effective transition to professional activity, which can be earned for the salary of a comprehensive rehabilitation complex, flight approaches. Object is reduction in the results of physical rehabilitation of football players aged 18–24 years with internal cartilage correction of the ankle joint at the outpatient stage by optimizing and increasing the effectiveness differentiated stasis of rehabilitation approaches that were obtained from the demanding process. Material and methods. the robot describes the results of monitoring 36 football players, which were carried out in the clinic of the Mir Majid Erslan Medical Center in Beirut (Lebanon). All injured athletes were man, ranging from 18 to 24 years, had closed ankle joint injuries of types A1, A2, C1 and C2 according to the AO/ASIF classification. The duration of the injury ranged from 4 weeks to 2 months. The main and control groups (18 injured athletes each) were identical in terms of age, manifestations of functional disorders, and localization of the received injuries. Injured athletes in the control group underwent a complex of rehabilitation sessions following the traditional physical rehabilitation program. Injured athletes of the main group received a comprehensive program of physical rehabilitation, which was integrated into the complex process of physical exercises, core kinesiotaping and modified Arabic procedures, treatment with elements of a similar massage. We assessed the effectiveness of physical rehabilitation using the LEFS scale, the Euro Qol-5D questionnaire, and the methods of A.V. Kalashnikov and NEER. Research data show that with overall positive dynamics, better results were recorded in injured athletes in the main group. Conclusions. with positive changes in the functional state of injured athletes in both clinical groups, the results were greater and significantly shorter than in the main group, and a comprehensive physical rehabilitation program was introduced This is due to the stagnation of coregual kinesiotherapy.